2018
DOI: 10.1007/s00590-018-2268-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage approach to total knee arthroplasty using colistin-loaded articulating cement spacer for vancomycin-resistant Pseudomonas aeruginosa infection in an arthritic knee

Abstract: A two-stage approach to TKA using a colistin-loaded articulating cement spacer can be used for an arthritic knee infected by vancomycin-resistant P. aeruginosa. Furthermore, local administration of colistin using a cement spacer can reduce the systemic side effects of colistin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The addition of an allograft, while it increases overall graft diameter, may have detrimental effects as studies have shown that processed grafts could negatively impact biomechanical properties and patient outcomes [4, 23, 24]. The association between processing techniques for allografts used in HY grafts and outcomes following primary ACLR was outside the scope of the present study comparing < 8 mm HA to ≥ 8 mm HY.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The addition of an allograft, while it increases overall graft diameter, may have detrimental effects as studies have shown that processed grafts could negatively impact biomechanical properties and patient outcomes [4, 23, 24]. The association between processing techniques for allografts used in HY grafts and outcomes following primary ACLR was outside the scope of the present study comparing < 8 mm HA to ≥ 8 mm HY.…”
Section: Discussionmentioning
confidence: 92%
“…However, prior studies have reported mixed results with some showing HY to have a higher risk of revision or worse functional scores when compared to HA, while others have found better outcomes with a HY or failed to observe a difference in outcomes between the two graft types. A recent meta‐analysis of these studies failed to observe a difference in graft failure and functional scores when comparing HA and hybrid grafts [4]. Unfortunately, these studies have small sample sizes or performed in an older patient population where the incidence of revision is lower and therefore a difference may not be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with a static antibiotic spacer and staged knee arthroplasty is effective [10][11][12][13]. The PJI literature has demonstrated articulating spacers to be superior [14,15] and supports using articulating spacers whenever the remaining bone and soft tissue allow.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported a two‐stage approach for the treatment of patients with infection and advanced knee arthritis with TKA implantation in the second stage [8, 13, 21, 27, 28, 30, 40]. An antibiotic cement spacer, as is used in the treatment of chronic infected TKA [24], was used in these patients.…”
Section: Introductionmentioning
confidence: 99%